COMPARISON OF ERYTHROCYTE PROFILES BETWEEN CATS FED WITH DRY COMMERCIAL AND TRADITIONAL FEED WITH MAGOT OIL AFFIX OF BLACK SOLDIER FLY - Irawati, Silvia; Gunawan, I Wayan Nico Fajar; Kendran, Anak Agung Sagung (Buletin Veteriner Udayana, 2022)
The provision of dry commercial feed and traditional feed with the addition of black soldier fly magot oil allows physiological changes to the animal's body.  The purpose of this study was to determine the profile of cat erythrocytes.  This study used a randomized block design (RAK) with four and the treatment consisted of six cats, with a total of 24 blood samples.  Dry commercial feed treatment as control (P0), dry commercial treatment with black soldier fly magot oil (P1), traditional treatment (P2), and black soldier fly magot oil (P3) traditional treatment.  The results of the examination data were analyzed using the variance test (ANOVA), to see the effect between treatments with Duncan's test.  The results of this study indicate that the administration of dry medicine and traditional feed added with black soldier fly magot oil was not statistically significantly different on total erythrocytes, hemoglobin, and packed cell volume.